Study on the Quality of Water in Some Streams of Cauvery River - Abida Begum; Harikrishnarai (E-Journal of Chemistry)
The quality of water in four streams of Cauvery River in Mandya District, where many small scale sugar and brewery distilleries are located, was analysed. Sampling was carried out from four streams designated as station 1 (upstream of effluent discharge point), station 2 (effluent discharge point) and station 3 (downstream of effluent discharge) station 4 (fresh water stream) to assess the impact of effluent on the water quality. The river water composition is increasingly dominated by Na and Cl in the downstream region of the river, indicating the influence of airborne salts with oceanic affinities. Significant spatial variation was observed in water level, transparency, turbidity, depth, dissolved oxygen, colour, biochemical oxygen demand, nitrate, nitrite and total hydrocarbon among the physiochemical parameters of the study stations. A posteriori test revealed that station 2 & 3 were the cause of the significant difference. The dissolved oxygen level in stations 2 & 3 was lower than 5.0mg/L, which is recommended minimum allowable limit for aquatic life. About 7 rotifer species in large amount recorded in this study were encountered in station 1, 7 in station 2 & 3 while 12 species in station 4. The overall density of rotifers in the four stations was significantly different. A posteriori comparison revealed that station 2 & 3 are the cause of the significant difference. The Branchionus angularis rotifers, which dominated the community, were found to tolerate the effluent effect in station 2&3, and showed remarkable recovery in the downstream station 4. Low faunal diversity and negative impact on the biotic and abiotic environment was experienced in station 2 & 3 throughout the duration of sampling because of the brewery effluent discharged directly into these two Streams.